Museos virtuales y la necesidad de un nuevo límite o excepción al derecho patrimonial de autor - Solórzano Solórzano, Raúl (2022)
Through this research, first a review of the definition of a museum is made, as well as its legal classification. Subsequently, the legislation on copyright applicable to museums is analyzed in order to determine the current possibilities of virtualization of the works that they have in on-site exhibition. Upon verifying the existing problems, the need for a new limitation or exception to the economic rights of author is raised to encourage the reproduction and public communication of works by museums and private collections to promote access to culture.